2016
DOI: 10.1080/10810730.2016.1193919
|View full text |Cite
|
Sign up to set email alerts
|

What Patient Characteristics Influence Nurses’ Assessment of Health Literacy?

Abstract: Overestimation of patients’ health literacy skills is common among nurses and physicians. At Vanderbilt University Hospital (VUH), nurses routinely ask patients the three Brief Health Literacy Screening (BHLS) questions. Data from two studies that recruited patients at VUH, the Health Literacy Screening (HEALS) study and the Vanderbilt Inpatient Cohort Study (VICS), were analyzed to compare the BHLS score recorded by nurses during clinical care with the score recorded by trained research assistants (RAs) durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(47 citation statements)
references
References 9 publications
2
45
0
Order By: Relevance
“…Furthermore, nurses in our study showed limited awareness of how to assess the health literacy in their patients and families, and therefore did not tailor information to enhance understanding. Other researchers have reported similar findings that nurses routinely overestimate patients' health literacy skills (Goggins, Wallston, Mion, Cawthon, & Kripalani, ). If patients and their families in the acute care setting do not comprehend the information provided to them by healthcare staff, they are unable to effectively exercise an informed choice when making healthcare decisions.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Furthermore, nurses in our study showed limited awareness of how to assess the health literacy in their patients and families, and therefore did not tailor information to enhance understanding. Other researchers have reported similar findings that nurses routinely overestimate patients' health literacy skills (Goggins, Wallston, Mion, Cawthon, & Kripalani, ). If patients and their families in the acute care setting do not comprehend the information provided to them by healthcare staff, they are unable to effectively exercise an informed choice when making healthcare decisions.…”
Section: Discussionsupporting
confidence: 52%
“…First, acute care nurses should be aware that the delivery of fundamental care is underpinned by the establishment of a relationship with patients and their family (Kitson et al., ). Caring relationships are underpinned by effective communication (Collins, ); therefore, nurses must be aware that people with lower individual health literacy may be less likely to ask questions, or to ask for clarification if they do not understand their care (Australian Commission on Safety and Quality in Health Care (ACSQHC), ; Goggins et al., ). If low health literacy is suspected, nurses should implement evidence‐based strategies such as (i) teach‐back (The Joint Commission, ); (ii) ask‐tell‐ask (Martino, ); or (iii) teach to a goal (Baker et al., ), to enhance patients' and families' understanding.…”
Section: Relevance To Clinical Practicementioning
confidence: 99%
“…Third, for the measure of health literacy, we relied on data collected by nurses as part of their normal workflow. As is often the case with data collected during routine care, the scores are imperfect, 45 but they have proven to be a valuable and valid indicator of health literacy in our previous research. 18,24,25,46 Fourth, we chose to declare a domain as positive if any item in that domain was positive and to perform a domain-level analysis (for greater clarity).…”
Section: Discussionmentioning
confidence: 97%
“…Health literacy (HL) is the degree to which people have the ability to understand and access basic health services information, prevent disease, and make and implement decisions during treatment in the process of acquiring health information [2,[8][9][10][11]. Low levels of HL indicate that health information is difficult to understand and that the instructions given are difficult and lead to adverse health outcomes [8,12,13].…”
mentioning
confidence: 99%